Rhipicephalus annulatus (Acari: Ixodidae) Control by Nigella sativa, Thyme and Spinosad Preparations - Shawky Mohamed Aboelhadid; Hesham A Mahran; Hazem M El-Hariri; Khalid Mohamed Shokier (Tehran University of Medical Sciences, 2016)
Background: Several compounds obtained from plants have potential insecticidal, growth deterrent or repellent characteristics. The control of hard ticks by non-chemical substances was targeted in this study. Methods: The effect of 36 materials on in-vitro ticks was studied, including 2 absolute controls (water only or absolute ethyl alcohol only), 6 conventionally used spinosad preparations (aqueous solutions), 12 Nigella sativa (N. sativa) preparations (aqueous and alcoholic solutions), and 12 Thyme preparations (aqueous and alcoholic solutions). The engorged ticks were tested in-vitro for mortality and oviposition ability using the studied materials. Results: The final mortality after 48 hours of application in N. sativa aqueous preparations began from 10.0% concentration, 1.0% to 100% by concentration preparations ≥10%. In addition, N. sativa alcoholic preparations began from 50.0% concentration, 2 % to 100% by concentration ≥5%. Meanwhile, Thyme aqueous and alcoholic preparations began from 70.0% concentration, 5% to 90% by concentration 10-20%. Additionally, spinosad aqueous preparations and both of control preparations (Water and Alcohol) resulted in no mortality. All differences were statistically significant. The oviposition was stopped in N. sativa (aqueous ≥10% and alcoholic ≥5%) and in spinosad (aqueous≥25%). The aqoues dilution of the used matters killed B. annulatus larvae beginning from the concentration 5%. Conclusion: Nigella sativa alcohol 20% was the best of studied preparations being the lowest concentration (20%) that could achieve the highest lethal (100%) effect in shortest time (12 hours). Moreover, Thyme oil and spinosad could not kill 100% of adult but did on larvae.